Otolith Growth Ring Pattern of Pangasius polyuranodon from Kampar and Siak River, Riau Province: Pola Lingkaran Pertumbuhan Otolith pada Ikan Juaro (Pangasius polyuranodon) di Perairan Sungai Kampar dan Sungai Siak Provinsi Riau - Yunita, Lauura Hermala; Wulanda, Yoppie; Ramdhani, Farhan; Heltria, Septy; Harjuni, Fiki; Windarti, Windarti; Fauzi, Muhammad (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2023)
Juaro (Pangasius polyuranodon) are found in the Kampar River and Siak River in Riau Province. The waters of the Kampar river are still in accordance with the quality standards and the waters of the Siak River are indicated by liquid waste pollution as evidenced by the results of air quality measurements, namely free CO2, BOD, Phosphate which are below the quality standard according to Government Regulation No. 82 of 2001. Decreased air quality can affect fish growth. and from the circular pattern of otolith growth. This study aims to determine the growth pattern of juaro fish in the waters of the Kampar and Siak rivers. This research was conducted in March – June 2019. The research method used a survey method. The otolith was sharpened using the Windarti (2013) method to see the growth circle pattern. Furthermore, the pattern and number of Dark Growth Circles (LPG) were seen using a microscope. 60 fish samples were taken (30 fish from the Kampar River and 30 from the Siak River). The results of the study showed that the LGP muscle of juaro fish from the Kampar River had 1 dark circle, while in the Siak River the darkest circle opened 3 pieces. These results concluded that the growth rate of juaro fish in the Kampar River and Siak River had experienced obstacles/disruptions in their lives.